A Wireless Interface for Prosthetic Controllers - Wells, David; O’Brien, Paul (CMBES Proceedings, 2007)
Currently, in order to fit and adjust powered prostheses, clinicians need to connect a prosthetic control system to a pc, requiring them to disassemble the prosthesis in order to connect the interface cables. This is inconvenient and time consuming for both the client and the clinician. An alternative to using a hardwired connection for accessing the control system inside a prosthesis was needed, since the hardwired connection effectively tethers a client to the pc, limiting the ability to move for testing and fitting the prosthesis. The cabling needed to be eliminated, and a wireless link was needed to perform the clinical adjustments that are necessary to optimize a client’s device. We have developed a wireless prosthetic control system as an alternative to using a fixed, hardwired connection to interface the controller in a client’s prosthesis to computer software for clinical fitting or evaluation. The new system uses wireless rf technology to eliminate the disadvantages of the hardwired connections. Wireless systems were developed for both the 928 MHz band and the 2.4 GHz band, and they are compatible with a prosthetic control software package currently used by clinicians around the world.